Isocitrate Dehydrogenase Inhibitors in Glioma: From Bench to Bedside - Merve Hazal Ser; Mason Webb; Anna Thomsen; Ugur Sener (MDPI AG, 2024)
Isocitrate dehydrogenase (IDH) mutant gliomas are a primary malignancy of the central nervous system (CNS) malignancies, most commonly affecting adults under the age of 55. Standard of care therapy for IDH-mutant gliomas involves maximal safe resection, radiotherapy, and chemotherapy. However, despite good initial responses to multimodality treatment, recurrence is virtually universal. IDH-mutant gliomas represent a life-limiting prognosis. For this reason, there is a great need for novel treatments that can prolong survival. Uniquely for IDH-mutant gliomas, the IDH mutation is the direct driver of oncogenesis through its oncometabolite 2-hydroxygluterate. Inhibition of this mutated IDH with a corresponding reduction in 2-hydroxygluterate offers an attractive treatment target. Researchers have tested several IDH inhibitors in glioma through preclinical and early clinical trials. A phase III clinical trial of an IDH1 and IDH2 inhibitor vorasidenib yielded promising results among patients with low-grade IDH-mutant gliomas who had undergone initial surgery and no radiation or chemotherapy. However, many questions remain regarding optimal use of IDH inhibitors in clinical practice. In this review, we discuss the importance of IDH mutations in oncogenesis of adult-type diffuse gliomas and current evidence supporting the use of IDH inhibitors as therapeutic agents for glioma treatment. We also examine unresolved questions and propose potential directions for future research.